Pengaruh Kualitas Layanan terhadap Loyalitas Melalui Variabel Kepuasan pada Lembaga Amil Zakat (Studi pada Baituzzakah Pertamina Kantor Pusat) - Nurul Musqari; Nurul Huda (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study was to determine the effect of service quality on customer loyalty through satisfaction variable in BAZMA Pertamina Office. Respondents were muzaki who distribute their zakah, infaq and shodaqoh through BAZMA. Total respondents 130 muzaki using purposive sampling, analysis using Structural Equation Modeling (SEM) with AMOS program. Results of this research, Service quality has positive effect and significant on satisfaction muzaki. Satisfaction has positif effect and significant on loyalty muzaki. Service quality has negative effect and not significant on loyalty muzaki.